Rethinking the Position of Islam and Indonesianness Amid Hopes for the Emergence of Multipolar Powers - Baedhowi Baedhowi; Sigit Tri Utomo; Nur Alfi Muanayah (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2022)
Globalization in the plurality of cultures and civilizations is a reality that cannot be denied in today's life. It's just that when the power played by the global world has been dominated by unipolar forces. What happens in it is an imbalance in various sectors of life, be it economic, political, socio-cultural, and physical-military. It is this unipolar power that, according to the author, is currently